Perencanaan Pendekatan Pembelajaran Deep Learning pada PAUD SKB Randong Tahun Ajaran 2025/2026 - Ferlina Elfiani; Gallex Simbolon; Frans Kristian Selly; Stofiani Susana Lima (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The purpose of this studi is: To determine the planning of the deep learning approach in Early Childhood Education SKB Randong, Compang Dalo Village, Manggrai. This studi uses qualitative research with descriptive methods, data collection techniques are carride out by observation, interviews, and documentation studies. The informants of this studi consist of the PAUD Program Implementation Coordinator and 2 PAUD teachers. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The techniques used to check the validity of the data in this studi area technical triangulation and source triangulation. Based on the result of the study, it can be conclude that the planinng of the deep learning approach in PAUD SKB Randong goes througj 4 stage, namely: (1) Identifcation of students readiness, material characteristics, and graduate profile dimansions: (2) Learning design includes learning objectives, paedagogical pratices, laerning partnership, learning environments, and utilization of digital technology: (3) Learning expriences are desigened based on the principles of awareness, meaning, and joyful through the stage of understanding, applying, and reflecting: (4) Formative and summativve assesments are qutilined in the in. Depth Learning Plan (RPM). So this research shows that deep laerning at PAUD SKB Randong has been imlemented systematically and strructured for in- Depth Learning of the.